Implementasi Kepemimpinan Kepala Madrasah Dalam Perspektif Trait Approach - Zikrul Hamdani (Al-Riwayah : Jurnal Kependidikan, 2024)
This study highlights the importance of leadership in Islamic educational institutions, particularly through the trait approach which emphasizes characteristics such as intelligence, maturity, achievement drive, and integrity. Using a qualitative approach and descriptive methods, this research was conducted at MTs Qur'aniyah Batu Kuta through observations and interviews with the school principal, school committee, teachers, and students, as well as utilizing data from school profiles and religious activity records. The findings indicate that these traits significantly contribute to the effectiveness of the madrasah principal's leadership, as evidenced by the principal's ability to make strategic decisions, manage resources and conflicts, design high-quality curricula, drive innovation, and maintain integrity and transparency in school management. This study offers practical contributions for the development of madrasah principals' leadership and provides theoretical contributions to the study of leadership in the context of Islamic education. It is expected to serve as a basis for the recruitment and professional development of prospective madrasah principals and to enhance the academic literature on leadership in Islamic education.